Glucocorticoids and Preterm Hypoxic-Ischemic Brain Injury: The Good and the Bad. (16th August 2012) - Bennet, Laura; Davidson, Joanne O.; Koome, Miriam; Gunn, Alistair Jan
Abstract : Fetuses at risk of premature delivery are now routinely exposed to maternal treatment with synthetic glucocorticoids. In randomized clinical trials, these substantially reduce acute neonatal systemic morbidity, and mortality, after premature birth and reduce intraventricular hemorrhage. However, the overall neurodevelopmental impact is surprisingly unclear; worryingly, postnatal glucocorticoids are consistently associated with impaired brain development. We review the clinical and experimental evidence on how glucocorticoids may affect the developing brain and highlight the need for systematic research.